Epidermal Growth Factor Receptor in Pancreatic Cancer - Melissa Oliveira‐Cunha; William G. Newman; Ajith K. Siriwardena (2011)
Pancreatic cancer is the fourth leading cause of cancer related death. The difficulty in detecting pancreatic cancer at an early stage, aggressiveness and the lack of effective therapy all contribute to the high mortality. Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein, which is expressed in normal human tissues. It is a member of the tyrosine kinase family of growth factors receptors and is encoded by proto-oncogenes. Several studies have demonstrated that EGFR is over-expressed in pancreatic cancer. Over-expression correlates with more advanced disease, poor survival and the presence of metastases. Therefore, inhibition of the EGFR signaling pathway is an attractive therapeutic target. Although several combinations of EGFR inhibitors with chemotherapy demonstrate inhibition of tumor-induced angiogenesis, tumor cell apoptosis and regression in xenograft models, these benefits remain to be confirmed. Multimodality treatment incorporating EGFR-inhibition is emerging as a novel strategy in the treatment of pancreatic cancer.